Moisture Content on Methane Desorption Characteristics in Coal and Its Effect on Outburst Prediction - Peng Li; Yaolin Cao; Xuelong Li; Fakai Wang; Zhongguang Sun; Qinke Huang; Deyou Chen (Advances in Civil Engineering)
Facts have proved that coal and gas outbursts require rapid desorption in a short period of time. Due to the limitation of experimental conditions, the methane desorption characteristics in the first few seconds (0–60 s) in coals with different moisture contents have not been fully studied at present. In this article, the initial desorption characteristics of methane in coals with different moisture contents were investigated using a self-developed experimental setup. In order to collect enough methane pressure data for analysis and calculation, a self-developed real-time data acquisition system with a time interval of about 10 ms was used in the experiment to calculate the initial gas desorption amount and the initial gas velocity diffusion index (ΔP). Experiments show that coal with low water content and methane outburst is more dangerous than coal with high water content and outburst; and the degree of outburst of coal and methane decreases exponentially with the increase of moisture content.